2019
DOI: 10.1186/s12917-019-1810-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a baculovirus-expressed capsid protein-based indirect ELISA for detection of porcine circovirus 3 IgG antibodies

Abstract: Background Porcine circovirus type 3 (PCV3), recently widely isolated from pigs with various clinical conditions, is likely globally epidemic. However, development of serological diagnosis for PCV3 in pigs is ongoing. Our objectives were to: 1) establish an indirect ELISA, using PCV3 capsid protein (Cap) prepared by Baculovirus Expression Vector System (BEVS) as a high-quality coating antigen for detection of PCV3-associated antibodies in serum samples; and 2) use this ELISA to conduct a serologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 34 publications
3
30
1
Order By: Relevance
“…Information related to PCV3 immune response is scarce, and field studies have shown high seroprevalence in growerfinisher, varying from 22-80 %, while seroprevalence in sows could reach 96 % [19,20], indicating a high level of virus circulation. However, the protective role of PCV3-induced antibodies is unknown and different isotypes could have a different role in viral neutralization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Information related to PCV3 immune response is scarce, and field studies have shown high seroprevalence in growerfinisher, varying from 22-80 %, while seroprevalence in sows could reach 96 % [19,20], indicating a high level of virus circulation. However, the protective role of PCV3-induced antibodies is unknown and different isotypes could have a different role in viral neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…B-cell epitopes located in the Cap protein (amino acid residues 93-103, 109-146, 170-181 and 192-202) and T-cell epitopes (amino acid residues 101-109, 113-121, 172-180 and 201-210) were predicted using the immune epitope database analysis resource (IEDB) [15]. In addition, recent studies have indicated the predicted potential linear epitope in the nuclear localization signal (NLS) sequence of the capsid [19]. However, the detection of PCV3 antibodies in swine sera has been successfully accomplished using the bacteria-expressed PCV3 capsid protein without NLS [3,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PCV2 VLPs are used as coating antigens to be able to detect serum neutralizing antibodies (SNAbs) in ELISA (Nainys et al 2014;Zhang et al 2016). Currently, PCV3 Cap proteins harvested from insect cells or E. coli have been used as antigens to detect PCV3-specific antibodies in an ELISA (Deng et al 2018;Zhang et al 2019). There is still lacking a VLP-based serological diagnosis method for PCV3.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional serological methods have been used to identify PCV3. These methods include an enzyme-linked immunosorbent assay that can accurately detect the viruses, but it can be time-consuming [14, 15]. Molecular methods based on polymerase chain reaction (PCR) assays, both routine and quantitative, have been developed to monitor and detect PCV3 rapidly and specifically [1618].…”
Section: Introductionmentioning
confidence: 99%